A Comparative Study of Nepali and English Phonology: Implications for Second Language Acquisition - Bohara, Bhuban Bahadur; Paneru, Narendra Raj (Innovative Research Journal, 2024)
This comparative study of the phonological systems of the Nepali and English languages uncovers the similarities and dissimilarities between the phonological systems of the Nepali and English languages and their implications for learning English by Nepali learners. Despite sharing Indo-European ancestry, Nepali (Indo-Iranian) and English (Germanic) stand significantly distant in phonology on different aspects: the segmental features of consonants, vowels, and consonant clusters; and suprasegmental features such as length, stress, intonation, pitch, tempo, juncture, and rhythm. Following Lado's (1957) Contrastive Analysis Hypothesis, Selinker's (1972) Interlanguage Theory, and Jarvis and Pavlenko's (2008) Cross-linguistic Influence, the analysis unearthed some of the major difficulties caused by interlinguistic disparities that affect intelligibility and fluency. In this context, an action-oriented pedagogical intervention is required since English has been considered an academic and socio-economic advancement of the students in a multilingual context of education in Nepal. Such interventions include phonetic drills, prosodic training, and pedagogical materials for effectively teaching English phonology.